POSTURE BIOMECHANICS OF CHILDREN WITH CEREBRAL PALSY: CURRENT STATE OF THE PROBLEM - Kholodov, S. A.; Hrebenina, A. A. (Rehabilitation and Recreation, 2023)
The purpose of the article is to study the current state of biomechanics of posture in children with cerebral palsy (CP). Research methods include theoretical analysis of special resources. Results. The human body is a complex biomechanical system in which various physical, chemical and biological subsystems interact in an organic unity. The result of such interaction are complex motor manifestations of its various functions. Motor function is one of the most important functions of the human body. The state of motor function reflects the ability of a specific biological system to capture, accumulate and transform various types of energy, substances and information. Musculoskeletal system performs many functions, but the most important among them is providing support, protection and movement of the human body. Each of these functions is characterized by different biological and, in particular, morphological structures. According to existing ideas, the symmetry of the biomechanical design is manifested due to the fact that this distribution of motor system masses in space allows a person to more effectively control gravitational interactions when moving his/her body. The most important concept related to the orientation of the human body in space and the entire set of motor actions is the spatial organization of the biolinks of its body. The spatial organization of the body is characterized by the biogeometric posture profile, the body shape, the proportions and type of body constitution, the topography of the force in different muscle groups. Bodily representation plays a special role in the assessment of an individual’s personal qualities, his/her psychological and cognitive characteristics, and serves as a starting point in recognizing an individual or excluding him/her from a social group. A person’s maintenance of a vertical body posture is accompanied by a micro-oscillatory process, constantly changing in the biokinematic pairs of the human body, where the skeletal-muscular system of a person plays a leading role. In recent years, thanks to the research of specialists, it has been proven that knowledge of biomechanical regularities of the spatial organization of body parts makes it possible to successfully manage the interactions of the body with the environment in order to preserve health, develop motor (physical) qualities and create normal conditions for human life. In the papers of modern researchers, a fairly complete overview of various research approaches to the study of the biomechanics of human posture is presented. Undoubtedly, each of the researchers has his own special view on the problem of posture biomechanics. Conclusions. Analysis of the results of numerous studies show that children with cerebral palsy have disorders of the posture biomechanics, namely changes in goniometric indicators of the body and vertical position.